2021
DOI: 10.1021/acs.jafc.1c04972
|View full text |Cite
|
Sign up to set email alerts
|

Fungus Polygalacturonase-Generated Oligogalacturonide Restrains Fruit Softening in Ripening Tomato

Abstract: Fruit softening exacerbates mechanical damage incurred during shipping and handling and the increase in pathogen susceptibility. Here, oligogalacturonides (OGs) produced by fungal polygalacturonase (PG) delayed fruit softening in tomato and maintained fruit firmness at 8.37 ± 0.45 N at 13 d of storage, which was consistent with the fruit firmness level of 5 d in the control groups. From RNA sequencing data in line production of phytohormones, we confirmed ethylene and jasmonic acid signals, the MAPK signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…65 Glucose metabolism plays a role in cell division, dilation and degradation, and contributes to fruit softening during ripening. 20,32,66 Endogenous glucanase, 67 PG, 68,69 expansion protein, 70,71 pectin methylesterase 72 and pectate lyase 73 have been reported to play important roles in cell degradation and fruit softening. In this study, ABA treatment induced the upregulation of most proteins associated with cell wall metabolism (especially PG).…”
Section: Discussionmentioning
confidence: 99%
“…65 Glucose metabolism plays a role in cell division, dilation and degradation, and contributes to fruit softening during ripening. 20,32,66 Endogenous glucanase, 67 PG, 68,69 expansion protein, 70,71 pectin methylesterase 72 and pectate lyase 73 have been reported to play important roles in cell degradation and fruit softening. In this study, ABA treatment induced the upregulation of most proteins associated with cell wall metabolism (especially PG).…”
Section: Discussionmentioning
confidence: 99%
“…Fruit firmness is one of the important characteristics of tomato fruit ripening, and the metabolism of the cell wall plays a crucial role in determining the change rate of fruit firmness during ripening [ 67 ]. Several enzymes, including endogenous glucanase [ 68 ], polygalacturonase (PG) [ 69 , 70 ], expansin [ 71 ], pectin methylesterase [ 72 ], and PL [ 73 ], were shown to be involved in cell wall metabolism and fruit softening [ 74 ]. In addition, Zeng et al [ 67 ] found that ABA treatment can accelerate fruit softening and promote the gene expression of β-galactosidase, SlTBG3 , and SlTBG4 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ectopic expression of FaPE1 promoted the content of aromatic amino acids phenylalanine, tryptophan, tyrosine, and aspartate. More recently, Yang et al [ 85 ] reported that OGs prepared from apple pectin through enzymatic digestion using a mixture of PG and PL from Botrytis cinerea inhibited fruit softening in ripening tomatoes. This research suggest that OGs are indeed capable of serving as signals to regulate plant growth and development.…”
Section: Cwi Signal Candidates In Fruit Ripeningmentioning
confidence: 99%